Laparoscopic repair for bilateral inguinal hernia. A technique that may be the standard in the future - Ielpo, Benedetto (Laparoscopic Surgery, 2019)
I want to thanks Ramia (1) and Piccinni (2) for their kind editorial to the paper I recently wrote with my colleagues at Ann of Surg (3). It is a great honor to be commented by such great surgeons.